AWARENESS OF CRYOTHERAPY IN SPORTS MEDICAL APPLICATIONS AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Cryotherapy is the use of cold for either the management of injury or illness, has become common across sports medicine. It remains a well-established procedure for managing serious soft tissue damages, however there is disparity between both the theoretical evidence for cryotherapy in clinical trials. This survey was performed for assessing the awareness about cryotherapy in sports medical applications amongst dental students. A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about cryotherapy in sports medical applications, their medicinal uses, anti-inflammatory activity, mechanism of action and side effects. The responses were recorded and analyzed. 87% of the respondents were not aware of medical uses of Cryotherapy.73% were not aware of anti-inflammatory activity of Cryotherapy.83 % were not aware of the mechanism of action of Cryotherapy. 85% were not aware of side effects of Cryotherapy. The awareness about the use of cryotherapy in sports medical applications is very less among dental students. Increased awareness programs and sensitization and continuing dental education programs along with greater importance to the curricular modifications in sports dentistry should be incorporated to improve the awareness levels.